We live - Miranda, Inaki; Miranda, Roy (Aftershock Comics LLC, 2020)
WHERE ALL IS LOST, HOPE IS FOUND. The year is 2084 and the world has changed. Wracked by calamities and crawling with monsters, the last remaining humans face a dangerous existence. And now, the Earth has been sent a message from the deepest reaches of space - a dark countdown to the extinction of all humanity. But there is hope! Five thousand children will be rescued by these mysterious message-senders. This is the journey of Hototo, one of the lucky five thousand - but only if his teenage sister, Tala, can safely deliver him to the nearest Extraction Beacon before time runs out. WE LIVE is a world of violence and beauty, a unique tale of the apocalypse as told by Inaki Miranda (Catwoman, Batman Beyond) and Roy Miranda, that invites both dread and hope